Pojęcie dowodu prywatnego i dokumentu prywatnego w polskim procesie karnym - Błażej Boch (Problemy Prawa Karnego, 2019)
The issues related to private evidence and documents in Polish criminal proceedings have for a long time been providing an impetus for many debates and disputes. In his text, the author analyses the opinions hitherto expressed in legal doctrine, and based on them he indicated how, in his opinion, the notions of “private evidence” and “private document” ought to be understood in accordance with the Code of Criminal Procedure. To this aim, he commences his consideration with an analysis of the notion of “evidence”, while stressing that it needs to be distinguished from such terms as “[a piece of] information” or “trace”. Further on, he discusses the distinction into “public [official]” and “private” evidence, and also presents his own definition of “private evidence” sensu stricto and sensu largo. Subsequently, the author proceeds to consider the notion of document in legal system, in particular in penal legal system, to eventually focus on the intended understanding of the notion of “private document” and the notion “reading aloud” included in Article 393 paragraph 3 of the Code of Criminal Procedure.